2018
DOI: 10.1080/02678292.2018.1519122
|View full text |Cite
|
Sign up to set email alerts
|

Orientational ordering of nanorods of different length in diblock copolymers

Abstract: Orientational and positional ordering of nanorods in the lamellae phase of diblock copolymers has been investigated using a simple theoretical model and dissipative dynamics simulations. Orientational order parameter and local concentration profiles of nanorods are calculated numerically and extracted from computer simulations data for different values of the nanoparticle length and different number of the interaction sites in the model nanorod. The predictions of the molecular theory are compared with the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…As shown in Figure , the average degree of orientation of the NC-grafted chains is larger than that of the FC-grafted chains, which indicates that the FC-grafted chains are more parallel to the interface as ε gA increases. This can be explained by the results of Osipov et al, who used the molecular theory to study the orientation of the rodlike symmetric particles in the lamellar phase of a diblock copolymer. They found that the particle is aligned parallel to the lamellar phase interface if both parts of the NP are in the compatible block and close to the interface because only in this configuration, both parts of the particle are in the compatible block, and the whole system is in the most stable state.…”
Section: Resultsmentioning
confidence: 98%
“…As shown in Figure , the average degree of orientation of the NC-grafted chains is larger than that of the FC-grafted chains, which indicates that the FC-grafted chains are more parallel to the interface as ε gA increases. This can be explained by the results of Osipov et al, who used the molecular theory to study the orientation of the rodlike symmetric particles in the lamellar phase of a diblock copolymer. They found that the particle is aligned parallel to the lamellar phase interface if both parts of the NP are in the compatible block and close to the interface because only in this configuration, both parts of the particle are in the compatible block, and the whole system is in the most stable state.…”
Section: Resultsmentioning
confidence: 98%
“…To date, a large number of papers have been published on this topic using various methods. [39][40][41][42][43][44][45][46][47][48][49][50][51] For example, Schultz et al used molecular dynamics to study the phase behaviour of composites based on diblock copolymers and spherical NPs. 39 Sides et al presented a hybrid particlefield simulation approach to investigate the equilibrium structure and properties of mesostructured polymeric fluids with embedded colloids and NPs.…”
Section: Introductionmentioning
confidence: 99%
“…50 Zhang et al studied cylindrical NPs in concentrated solutions of diblock copolymers. 43 The local distribution and orientational order of anisotropic nanoparticles (nanorods) in diblock copolymers as a function of their length, stiffness, and selectivity were studied by Berezkin et al 44,45 More recently, this issue has also been investigated by Diaz et al 51 who have shown that the morphology of block copolymers can be modified at modest concentrations of anisotropic NPs.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Subsequently, a series of relevant studies have been conducted using different methods. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Liang et al investigated mixtures of symmetric diblock copolymers/rigid nanorods, [4] cylindrical diblock copolymers/rigid nanorods [5] and mixtures of diblock copolymers and mono-or bidisperse nanorods [6] via dissipative par-ticle dynamics (DPD) simulation. This method has also been used to investigate the structure and dynamics of the selfassembly of bundles formed by nanorods of different flexibilities in the gyroid phase of the diblock copolymer matrix, [7] as well as to study the mechanism by which the nanorod surface properties regulate the compatibilization behavior and morphology transition in demixing polymer blends.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Langevin field theoretic simulation is a useful approach to study the distribution of nanorods in diblock copolymer thin films. [15] Osipov et al studied the orientation ordering and spatial distribution of nanorods [16] as well as nanorods of various lengths [17] in the lamellae phase of diblock copolymers using both molecular statistical theory and DPD simulations.…”
Section: Introductionmentioning
confidence: 99%